1996
DOI: 10.1210/mend.10.5.8732688
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of insulin signal transduction by eutopic overexpression of the receptor-type protein-tyrosine phosphatase LAR.

Abstract: Protein-tyrosine phosphatases (PTPases) regulate insulin signaling by catalyzing the tyrosine dephosphorylation of the insulin receptor and its substrate proteins. Previous studies have implicated a PTPase localized to a cell membrane fraction in the regulation of the insulin receptor in situ. LAR (leukoyte antigen related) is a transmembrane PTPase in insulin-sensitive tissues with in vitro catalytic specificity for the insulin receptor kinase domain. When transfected into Chinese hamster ovary cells overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Consistent with these results, overexpression or antisense suppression studies of LAR showed that this rPTP could negatively regulate IR, IRS‐1 and Shc phosphorylation, as well as the PI3‐kinase and MAPK pathways [35–37]. In CHO‐hIR cells expression of LAR reduced insulin stimulated tyrosine phosphorylation of IR and IRS‐1, as well as DNA synthesis [38]. Importantly, proper membrane localization of LAR seems to be required, as expression of the cytoplasmic domain of LAR alone does not recapitulate these effects.…”
Section: Larmentioning
confidence: 70%
“…Consistent with these results, overexpression or antisense suppression studies of LAR showed that this rPTP could negatively regulate IR, IRS‐1 and Shc phosphorylation, as well as the PI3‐kinase and MAPK pathways [35–37]. In CHO‐hIR cells expression of LAR reduced insulin stimulated tyrosine phosphorylation of IR and IRS‐1, as well as DNA synthesis [38]. Importantly, proper membrane localization of LAR seems to be required, as expression of the cytoplasmic domain of LAR alone does not recapitulate these effects.…”
Section: Larmentioning
confidence: 70%
“…On the other hand, aged ptp1b null mice present a leaner phenotype than wild type mice and are protected against ageassociated insulin resistance (Gonzalez-Rodriguez et al, 2012), and neuronal-specific PTP1B Knockout mice have reduced weight and adiposity as well as increased physical activity and energy expenditure (Bence et al, 2006). Tyrosine-phosphorylated insulin receptor can also be dephosphorylated by LAR (Hashimoto et al, 1992) which has been shown to be a negative modulator of insulin action implicated in insulin resistance states (Kulas et al, 1995;Zabolotny et al, 2001;Zhang et al, 1996). Nevertheless, other authors observed that the decrease of LAR protein tyrosine phosphatase induces insulin resistance and defects in glucose homeostasis (Mander et al, 2005;Ren et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For example, tyrosine phosphorylation is a key reaction in the initiation and propagation of insulin action (Myers and White, 1996;White and Kahn, 1994). Thus, PTP1B (Ahmad et al, 1995;Kenner et al, 1996;Kole et al, 1996), LAR (Kulas et al, 1995;Zhang et al, 1996) and PTBa (Lammers et al, 1997;Moller et al, 1995) have been implicated as negative regulators of insulin receptor signaling. Consequently, protein phosphatase inhibitors may have use in the treatment of diabetes and obesity.…”
Section: Introductionmentioning
confidence: 99%